On the Possibilities of Researching the Marriage Policies of the Rurikids: The Case of Mstislav Fyodor Vladimirovich Monomakhovich - Dąbrowski, Dariusz (Studia Ceranea, 2018)
The main goal of the article is to present the possibilities and methods of research on the Rurikid’s matrimonial policy in the Middle Ages on the example of a selected group of princes. As the subject of studies were chosen Mstislav Vladimirovich and his children. In total, 12 matrimonial relationships were included. The analysis of the source material revealed very unfavorable phenomena from the perspective of the topic under study. The Rus’ primary sources gave information on the conclusion of just four marriages out of twelve. The next four matrimonial arrangement inform foreign sources (Scandinavian and Norman). It should be emphasized particularly strongly that – save for two exceptions of Scandinavian provenance – the sources convey no information whatsoever as regards the political aims behind this or that marriage agreement. It appears, then, that the chroniclers of the period and cultural sphere in question did not regard details concerning marriages (such as their circumstances or the reasons behind them) as “information notable enough to be worth preserving”. Truth be told, even the very fact of the marriage did not always belong to this category. Due to the state of preservation of primary sources the basic question arises as to whether it is possible to study the Rurikids’ matrimonial policy? In spite of the mercilessly sparse source material, it is by all means possible to conduct feasible research on the Rurikids’ marriage policy. One must know how to do it right, however. Thus, such studies must on the one hand be rooted in a deep knowledge of the relevant sources (not only of Rus’ provenance) as well as the ability to subject them to astute analysis; on the other hand, they must adhere to the specially developed methodology, presented in the first part of the article.